Characterization of Fly Ash from Coal-fired Steam Power Plant Tarahan, Lampung, and Its Potential as a Soil Amendment - Mutaqin, Adiksa Insan; Chaerul, Mochammad (Research and Social Study Institute, 2025)
Background: Fly ash, a byproduct of coal combustion in steam power plants, has significant potential for utilization, particularly as a soil amendment. However, in Indonesia, including at the Tarahan coal-fired steam power plant (PLTU Tarahan), most fly ash remains underutilized and is primarily disposed of in landfills.Aims: This study aimed to analyze the characteristics of fly ash produced at PLTU Tarahan and evaluate its potential for recycling through three utilization pathways: biosilica production, application as a soil-stabilizing agent, and incorporation into compost mixtures.Methods: Samples were collected from three distinct locations and analyzed at a certified laboratory using standardized procedures. The resulting data were subsequently compared with values reported in existing literature and interpreted using a descriptive analytical approach.Result: Characterization results indicated that the fly ash belongs to Class F, with high silica (SiO₂) content and low calcium oxide (CaO), making it pozzolanic but non-cementitious. Each reuse pathway was assessed in terms of technical compatibility, infrastructure readiness, pretreatment requirements, market potential, and environmental risk mitigation. The findings showed that biosilica production offers high added value but requires advanced chemical extraction technology. Soil stabilization using fly ash and lime is technically feasible for internal infrastructure and land reclamation projects, offering immediate benefits with minimal pretreatment. When mixed with organic materials such as press mud or combined with garbage enzyme, fly ash also enhances compost maturity, nutrient content, and enzymatic activity. Based on these results, a phased implementation strategy is recommended, beginning with applications that are low-risk and compatible with existing infrastructure. These findings contribute to the development of more adaptive and sustainable fly ash management strategies within coal-fired power plants. To support practical implementation, further laboratory- and field-scale studies are needed to validate long-term performance. Additionally, future research should incorporate multicriteria decision-making approaches, such as the Analytic Network Process (ANP), to comprehensively evaluate technical, environmental, social, and economic factors in selecting the most appropriate utilization pathway.